2021
DOI: 10.3390/molecules26185475
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Umbrella as a Nanocarrier for Antifungals

Abstract: A molecular umbrella composed of two O-sulfated cholic acid residues was applied for the construction of conjugates with cispentacin, containing a “trimethyl lock” (TML) or o-dithiobenzylcarbamoyl moiety as a cleavable linker. Three out of five conjugates demonstrated antifungal in vitro activity against C. albicans and C. glabrata but not against C. krusei, with MIC90 values in the 0.22–0.99 mM range and were not hemolytic. Antifungal activity of the most active conjugate 24c, containing the TML–pimelate link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In vitro , its activity was assessed in the MIC 90 range of 0.22–0.99 mM against C. albicans and C. glabrata (Table ). Skwarecki et al showed that conjugates containing a dihedral molecular umbrella can penetrate the cell wall in Candida cells. This allows further research to construct more active conjugates with molecules other than cispentacin. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro , its activity was assessed in the MIC 90 range of 0.22–0.99 mM against C. albicans and C. glabrata (Table ). Skwarecki et al showed that conjugates containing a dihedral molecular umbrella can penetrate the cell wall in Candida cells. This allows further research to construct more active conjugates with molecules other than cispentacin. , …”
Section: Resultsmentioning
confidence: 99%
“… Skwarecki et al showed that conjugates containing a dihedral molecular umbrella can penetrate the cell wall in Candida cells. This allows further research to construct more active conjugates with molecules other than cispentacin. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] Candidiasis has been investigated as the most common mycosis, and C. albicans has been ranked as the fourth most common causative organism of nosocomial infections (Candidiasis) globally. [11][12][13] Although currently, available antifungal drugs such as polyenes, azoles, allylamines, echinocandins, and antimetabolites have been helpful in many circumstances, they suffer from a confluence of systemic toxicities (such as hydrophobicity, poor pharmacokinetics, and -dynamics, low bioavailability, systemic side effects) and escalating resistance that hinders their therapeutic efficiency. [14] These limitations of existing antifungal drugs have been overcome by formulation methods of novel antifungal drugs, [14] improvements of existing antifungal drugs, [14] combination therapy, [14] and efficient delivery approaches for antifungal drugs.…”
Section: Introductionmentioning
confidence: 99%